The knowledge, attitude and practices of COVID-19: a survey among medical students in the East Coast of Peninsular Malaysia Public Medical Schools - Aidid, Edre Mohammad; Syed Ahmad Alsagoff, Sharifah Aishah; Anuar, Muhamad Azamin; Abu Bakar, Asrar; Taib, Fahisham; Yusof, Muhammad Zubir; Syed Abd Hamid, Syed Abdul Khaliq; Abas, Muhammad Ihsanuddin (Universiti Sains Malaysia, 2022)
COVID-19 has affected university medical students, resulting in the new norm of learning and practice. Understanding these students’ knowledge, attitude and their practice would be essential as they would serve as the future doctor in Malaysia. The study attempted to evaluate medical students’ knowledge, attitude and practice (KAP) in the east coast states of Peninsular Malaysia. An online and multi centre cross-sectional study was undertaken among all the three public medical schools in the east coast region of Peninsular Malaysia, between 8th July to 21st July 2020. The questionnaire consisted of sociodemographic data and the three domains which included COVID-19 KAP. Students were invited to participate via social media platform such as WhatsApp and students’ email. A total of 1,008 medical students voluntarily participated in the study with female to male ratio of 2.6:1. A total of 356 (35.3%) of the medical students had satisfactory knowledge score, with 75% of them were female. The majority of the students had positive attitude towards COVID-19 and practiced meticulous social distancing during the pandemic. We noted that seniority influenced knowledge score, and this was evident as 264 (26.2%) of the students were in their clinical year. Overall, the knowledge scores regarding COVID-19 among the medical students in East Coast of Peninsular Malaysia was reasonable and there were opportunities to augment these standards. Meticulous plans are needed to enhance knowledge and preparedness of the current crops of medical students to be competent future frontliner for Malaysia.